Echinocandin-resistant Candida tropicalis Bloodstream Infections. (4th October 2017) - Sfeir, Maroun; Jiménez-Ortigosa, Cristina; Schuetz, Audrey; Jenkins, Stephen; Jones, Sian; Soave, Rosemary; Van Besien, Koen; Satlin, Michael; Small, Catherine; Perlin, David; Walsh, Thomas
Abstract: Background: The aim of this study is to describe the clinical manifestations, molecular mechanisms, and treatment outcomes of patients with echinocandin-resistant Candida tropicalis ( C. tropicalis ) bloodstream infections (BSI). Methods: A PubMed search was conducted using the search terms related to C. tropicalis BSI and echinocandin resistance. Two previously unreported cases from our institution diagnosed with C. tropicalis BSI that developed resistance to echinocandins were also included. Demographics, comorbidities, treatment, clinical outcomes, and molecular mechanisms were analyzed. Results: Seven patients with echinocandin-resistant C. tropicalis BSI were identified, including 5 previously reported cases and two from our institution. Median age was 58.7 ± 20.4 years; 3 (43%) patients were males. Three (43%) had acute myelogenous leukemia, 3 (43%) had acute lymphoblastic leukemia, and 1 (14%) had urothelial cancer. All patients were immunocompromised having received chemotherapy in the last six months and 3 (43%) were hematopoietic stem cell transplant recipients. Five (71%) had breakthrough of echinocandin resistance while receiving an echinocandin; one (14%) received caspofungin in the past 3 months and only one (14%) had no reported echinocandin exposure in the past 3 months. DNA sequencing of the FKS1 gene for mutations known to confer echinocandin resistance was performed in 4 cases, including our two index cases. Homozygous T-to-C mutations in two alleles of FKS1 gene was detected in 2 cases, and a heterozygous mutation was detected in the other 2 cases, which resulted in a deduced serine-to-proline amino acid change at position 654 (S654P). Six patients (86%) survived after being treated with an antifungal agent other than an echinocandin. Treatment was changed to liposomal amphotericin B in two cases, and one each to voriconazole, fluconazole, voriconazole plus liposomal amphotericin B, and caspofungin plus voriconazole. The one patient who died received intravenous voriconazole. Conclusion: Echinocandin resistance emerged in neutropenic patients with C. tropicalis fungemia through a characteristic mutational hot-spot amino acid change in the target FKS1 gene. Although alternative antifungal agents may be successfully used as salvage therapy, the outcome may still be fatal. Disclosures: D. Perlin, Pfizer: Research support, honoraria and/or consulting fees and/or has served on advisory board, Research support, honoraria and/or consulting fees and/or has served on advisory board. Astrellas: Research support, honoraria and/or consulting fees and/or has served on advisory board, Research support, honoraria and/or consulting fees and/or has served on advisory board. Merck: Research support, honoraria and/or consulting fees and/or has served on advisory board, Research support, honoraria and/or consulting fees and/or has served on advisory board. Cidara: Research support, honoraria and/or consulting fees and/or has served on advisory board, Research support, honoraria and/or consulting fees and/or has served on advisory board. Synexis: Research support, honoraria and/or consulting fees and/or has served on advisory board, Research support, honoraria and/or consulting fees and/or has served on advisory board. F2G: Research support, honoraria and/or consulting fees and/or has served on advisory board, Research support, honoraria and/or consulting fees and/or has served on advisory board. Myconostica: Research support, honoraria and/or consulting fees and/or has served on advisory board, Research support, honoraria and/or consulting fees and/or has served on advisory board. Amplyx: Research support, honoraria and/or consulting fees and/or has served on advisory board, Research support, honoraria and/or consulting fees and/or has served on advisory board. Matinas: Research support, honoraria and/or consulting fees and/or has served on advisory board, Research support, honoraria and/or consulting fees and/or has served on advisory board. GAFFI: Scientific Advisor, Advisor. Bill and Melinda Gates Foundation: Scientific Advisor, Advisor